The effect of work family conflict and workload on work stress in affecting turnover intention - Gebby Gebby; Hari Hari; Reni Reni (Jurnal Mantik, 2023)
The development and economic growth of the Indonesian people in today's increasingly modern era of globalization has made work the main factor in meeting human needs and improving the quality of human life. Currently, work has become the main requirement for every human being, both men and women who are married or have a family. This can lead to multiple roles or commonly known as work family conflict. If an individual already has work family conflict, it will increase the workload they have and will cause work stress which can lead to turnover intention. This study aims to examine the effect of work family conflict and workload on work stress which affects turnover intention in employees of PT GCU Jakarta Head Office. This study uses a quantitative approach to the survey method. The subjects of this study were 130 employees of PT GCU, Jakarta Head Office. Data analysis techniques using structural equation models (SEM) assisted with the SmartPLS version 4.0 software program. The results of this study indicate that all variables have positive effect to each other. The research shows there is an implication between the results and affect event theory. The emotional that employees have might be influence their work when they are not unable to balance the stress of their work and their family. The suggestion to future research is to analyze what the company can do to decrease turnover intention rate because of work family conflict in their employees